1979
DOI: 10.1161/01.cir.60.6.1343
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in variant angina pectoris. Relationship of arrhythmias to ST-segment elevation and R-wave changes.

Abstract: SUMMARY Twenty-six patients with variant angina pectoris (VAP) were studied 1) to determine whether the degree of ST-segment elevation and R-wave changes correlate with the development of arrhythmias; and 2) to evaluate the relationship between the prevalence of arrhythmias, the severity of coronary artery disease, left ventricular function and wall motion.Serious arrhythmias were found in 12 patients (46%) (ventricular fibrillation in two, ventricular tachycardia in four, ventricular premature complexes [VPCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

1980
1980
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 40 publications
1
12
0
3
Order By: Relevance
“…Ventricular arrhythmias are found in up to 50% of patients with documented coronary spasms and may be attributed to either vascular occlusion or reperfusion [14]. The incidence of ventricular arrhythmias is correlated with the severity of ischemia (duration and extent of ST elevations) but does not seem to be influenced by the site of ischemia, the presence or extent of fixed coronary stenoses, left-ventricular function, or the patient's age or sex [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventricular arrhythmias are found in up to 50% of patients with documented coronary spasms and may be attributed to either vascular occlusion or reperfusion [14]. The incidence of ventricular arrhythmias is correlated with the severity of ischemia (duration and extent of ST elevations) but does not seem to be influenced by the site of ischemia, the presence or extent of fixed coronary stenoses, left-ventricular function, or the patient's age or sex [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with calcium antagonists and organic nitrates has been recommended in patients with coronary spasm [18] as well as in those with spasminduced arrhythmias [3,7,9,19]. However, recommendations have not yet been made as to dosage and alternative treatments, and comparative studies are lacking because of the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] To our knowledge, however, no quantitative data have been reported on the diurnal distribution of ischemic episodes, such as chest pain and ECG changes, in variant angina except for a preliminary report by Kuroiwa,4 which showed a higher frequency of recurrent ST-segment elevations early in the morning. It is important to clarify the diurnal distribution of the episodes for the evaluation of pathophysiology of variant angina as well as for treatment.…”
mentioning
confidence: 98%
“…1 Furthermore, in a recent review of the arrhythmias which accompany coronarv artery spasm, Kerin et al (23,24) noted that the arrhythmias freQuently occurred at a time when the ischemia induced ST segment elevation was beginning or had completely normalized. Thus, these authors concluded that some of these arrhythmias may have resulted from a reperfusion mechanism.…”
mentioning
confidence: 99%